2020
DOI: 10.1039/d0na00755b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the chemical exfoliation of lithium cobalt oxide using UV-Vis spectroscopy

Abstract: Two-dimensional materials have been at the forefront of chemistry and materials science research for the past decade owing to promising applications across many fields. Improvements in exfoliation processes continually give...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…[11] It was not until 2009 that the exfoliation of lithium cobalt oxide (LCO) was first reported (Kim et al [62]). Since then only a few groups have reported further on this topic [55,56,[62][63][64][65][66][67][68][69][70][71][72] (many coming from our research group [55,56,[63][64][65] leaving the exfoliation of LCO relatively underexplored.…”
Section: Chemical Exfoliation Of Lixcoo2 Nanosize Flakesmentioning
confidence: 99%
“…[11] It was not until 2009 that the exfoliation of lithium cobalt oxide (LCO) was first reported (Kim et al [62]). Since then only a few groups have reported further on this topic [55,56,[62][63][64][65][66][67][68][69][70][71][72] (many coming from our research group [55,56,[63][64][65] leaving the exfoliation of LCO relatively underexplored.…”
Section: Chemical Exfoliation Of Lixcoo2 Nanosize Flakesmentioning
confidence: 99%
“…As CONs can be obtained by further exfoliation of the centrifuged powder by the simple addition of deionized water to the powder slurry and are not mentioned in the exfoliation studies of LCO. 21,[23][24][25][26][27][28][29][30][31][32][33][34][35] Upon addition of deionized water, indications of exfoliation are immediately observed, as supported by the presence of a dark solution that survives low-speed centrifugation. The behavior can be explained by an influx of water molecules into the interstices of the TMA-swelled layered cobalt oxide structure.…”
Section: Cons In Ph-neutral Aqueous Solutionsmentioning
confidence: 99%
“…Most commonly exfoliated from lithium cobalt oxide (LCO) 21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] (with many reports coming from our research group [23][24][25]28,29,34,36 ), CONs have been implemented in Liion batteries, thermoelectric devices, armored polymer particles, and layer-by-layer films. 21,23,27,30,31 CONs have also been synthesized through bottom-up techniques, but are not the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] Cobalt oxide nanosheets (CONs) produced from the chemical exfoliation of, e.g., lithium cobalt oxide (LCO), and are a relatively understudied class of 2D particle surfactants but of great interest for potential catalytic, electrochemical, and superconductive properties. [32][33][34][35][36][37][38][39] Limited studies have reported the use of cobalt oxide materials in emulsions. One example is the use of oil-in-water (o/w) Pickering emulsions to prepare composites of LCO nanoparticles and polyaniline as the positive electrode in a lithium battery; the discontinuous phase of the emulsion was aniline dissolved in toluene and LCO particles served as surfactant.…”
Section: Introductionmentioning
confidence: 99%